Perancangan Dashboard untuk Analisis Penjualan pada Perusahaan X - Nathanael Gumarus; Dedi Trisnawarman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Company X is one of the companies engaged in the food processing industry, requires a data management system that can produce accurate information in supporting sales activities. Therefore, this research aims to design a dashboard using the Business Intelligence Roadmap approach. In the analysis process using the Time Series Moving Average method to perform the sales forecasting process and clustering for product grouping. The stages of this research begin with the identification of problems related to this research and the collection of sales data for 3 years (2022-2024). The obtained data is then processed through the ETL (Extract, Transformation, Load) process using Pentaho Data Integration and visualized using Power BI Desktop. The results of this study are in the form of an interactive dashboard designed as a tool for monitoring and analyzing sales to help companies make more informed and effective business decisions.